Extra! Extra! A burlette by Artur Azevedo and Eduardo Garrido just published! (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
Review of the burlette Pum!, a play by Artur Azevedo and Eduardo Garrido. This is an unpublished play, written and performed in the late 19th century in Brazil, in the context of the Armada Revolt (1893-1894). The work is the result of a research carried out by the historian Tania Brandão, in partnership with professor Diógenes Maciel, who together rescued and edited a previously unpublished brazilian burlette, whose survival over time occurred through the risky transit between drawers, collections and hands. With the recent publication of Pum! by Editora Papel da Palavra (2024), readers, students and theater artists will be able to delight in a work that reinforces the greatness of the national theater with its comic, musical and popular tradition.
Keywords: publication of dramaturgy; Artur Azevedo; Eduardo Garrido